The Impact of Foreign Language Anxiety on the Utterance Fluency of International Students in the UK: Does the Presence of an Audience Matter? Does the presence of an audience matter? (ICFSLA 2023) - Stokes, Jasrael D. (Theory and Practice of Second Language Acquisition, 2025)
Foreign language anxiety (FLA) can have a detrimental impact on language production, which can have dire consequences for students completing a degree in a language other than their mother tongue. Studies have shown speakers to cope with FLA by using time-gaining mechanisms, manifesting in utterance disfluencies. Research exploring the mechanisms in which FLA impacts oral fluency measures is limited particularly among learners completing a degree abroad immersed in the target language, where FLA can impact life both inside and outside of the classroom. The current study investigated the impact of FLA on the English utterance fluency of international students undertaking a degree in the UK and examined how the presence of native-speaker listeners affected this relationship. After the completion of questionnaires regarding FLA, the participants took part in an online Zoom call and completed a monologue-style speaking task. They were randomly allocated to either a control condition or an experimental condition, which had four native-speaker listeners in the audience. Speech samples for the speaking task were then analyzed for utterance fluency variables. The results showed that the participants scoring higher on FLA produced a significantly higher percentage of utterance disfluencies while speaking. Contrary to expectations, the participants allocated to the control condition were no less anxious than participants in the experimental condition, indicating possibly high FLA merely due to the requirement of speaking. The findings of this study provide important implications for educators in understanding how FLA may impact students’ utterance fluency when required to speak in class.